A New Aqli Naqli Indexing Content Psycho Lingusitic Semantique-Spiritual Training For Sustainable And The Happiness Ummah By Using Metodology Of Al-Tawlidiah "atAwm And mGG" - Asma Abdul Rahman; Ahmad Abdul Rahman (International Journal Development Research, 2024)
Non-Indexed Publication